A low proportion n-6/n-3 PUFA diet supplemented with Antarctic krill (Euphausia superba) oil protects against osteoarthritis by attenuating inflammation in ovariectomized mice. Issue 15 (22nd June 2021) - Dai, Yufeng; Zhang, Lei; Yan, Ziyi; Li, Zhuo; Fu, Meng; Xue, Changhu; Wang, Jingfeng
Abstract : The low proportion n-6/n-3 PUFA diets, particularly with AKO, alleviated inflammation and inhibited articular cartilage degeneration in ovariectomized mice. Abstract : Osteoarthritis (OA), the most common form of arthritis, is characterized by cartilage destruction, and its incidence is much higher in the osteoporotic population. There is increasing evidence that the occurrence and development of OA are modulated by the dietary intake of polyunsaturated fatty acids (PUFA). This study investigated the effects of dietary PUFA, including n-3/n-6 PUFA proportion and the molecular form of n-3 PUFA, on OA using osteoporotic osteoarthritis dual model mice, where phospholipid type n-3 PUFA were specifically examined. The results revealed that a low proportion of n-6/n-3 PUFA in diets from 1 : 1 to 6 : 1 significantly improved the cartilage structure and inhibited articular cartilage polysaccharide loss. Furthermore, the low proportion n-6/n-3 PUFA diets inhibited the NF-κB signaling pathway by activating G-protein coupled receptor 120 (GPR120) to reduce inflammation and inhibit catabolism. Antarctic krill ( Euphausia superba ) oil (AKO), rich in phospholipid-type n-3 PUFA, had a better effect on OA than linseed oil (plant-derived n-3 PUFA), which may be due to peroxisome proliferator-activated receptor-gamma (PPAR γ). These findings suggested that the low proportion n-6/n-3 PUFA diets, particularly with AKO, alleviated inflammation and inhibited articular cartilage degeneration. Therefore, dietary intervention can be a potential treatment for OA.